The changing transition to adulthood leaving and returning home - Goldscheider, Frances K.; Goldscheider, Calvin; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
Examines the reasons why children ultimately leave home to live on their own and how the pattern has changed throughout the 20th century.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Young adults -- United States -- Psychology; Adult children -- United States -- Psychology; Families -- United States; Home -- United States; Electronic books